2021
DOI: 10.4025/actascianimsci.v43i1.50587
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of vegetable oils in diets of broiler chicken raised in hot weather and effects on antioxidant capacity, lipid components in the blood and immune responses

Abstract: The aim of this study was to assess the effects of vegetable oils on the antioxidant capacity, blood lipid components and immune responses in chickens raised in hot climate. In a completely randomized design, 300 chicks were assigned to four treatments and five replicates with 15 chicks per each. The highest concentration of malondialdehyde was found in broilers fed palm oil (p < 0.05). Chickens fed corn oil had the lowest and those fed flaxseed oil had the highest antioxidant enzymes activities (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…According to Mujahid et al [45], the addition of 6.7% olive oil to the diet of broiler chickens reared under thermo-neutral or heat-stress conditions reduced mitochondrial ROS production and decreased oxidative damage in the birds. Recent feedings trials performed in broilers reared at high ambient temperatures revealed the antioxidant effect of olive oil and the improvement of the birds' immune system [46], the improvement of hormonal indicators and chickens' performances as well as the increased activity of heat tolerance genes in chickens [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Mujahid et al [45], the addition of 6.7% olive oil to the diet of broiler chickens reared under thermo-neutral or heat-stress conditions reduced mitochondrial ROS production and decreased oxidative damage in the birds. Recent feedings trials performed in broilers reared at high ambient temperatures revealed the antioxidant effect of olive oil and the improvement of the birds' immune system [46], the improvement of hormonal indicators and chickens' performances as well as the increased activity of heat tolerance genes in chickens [47].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the review of the literature shows that there are currently no data available on the dietary impact of OP on the thermal comfort of broilers. In contrast, there are a few studies on the nutritional effects of various by-products such as olive oil [45][46][47] and olive leaves [48,49] on heat stress in chickens. Recent nutritional studies in broilers reared at high ambient temperatures have demonstrated the antioxidant effect of olive oil [45,46], improved birds' immune system [46], improved hormonal indicators and chick performance and the increased activity of genes responsible for the birds' thermal resistance [47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil and fat sources are important energy sources, and they are normally included, at levels of up to 5%, in broiler feed [ 103 ]. The freshness of oil and fat sources is important in poultry feed because oxidized oil and fat can induce lipid peroxidation and oxidative stress in animals [ 104 ].…”
Section: Challenging Conditions In Broiler Production Are Associated ...mentioning
confidence: 99%